Biodiversity of Keratinophilic Fungal Flora in University Campus, Jaipur, India - Meenakshi Sharma; Neetu Jain (Iranian Journal of Public Health, 2012)
Background: Soil is well known to support the transient or ongoing existence of keratinophilic fungi and potential source of infection for human and animalsMethods: Samples were collected from 67 sites of university campus like PG study centers, playgrounds, gardens, hostels, administrative blocks, library, bank, canteen and road side for the estimation of keratinophilic fungi using the hair baiting technique.Results: Totally, 192 isolates belonging to 14 genera and 21 species were reported. Soil pH range varies from 6.5 to 9.0 pH. Most of the fungi isolated from neutral to slightly alkaline soil. Chrysosporium tropicum (20.83%) was the most predominant fungi reported from all sites. Trichophyton mentagrophytes (15.10%) was the second most commonly reported fungi. Chrysosporium indicum (11.45%), T. simii (9.37%), C.evolceanui (8.83%) T. terrestre (4.68%) and Cephaliophora irregularies (4.68%) were frequently reported. Microsporum audouinii, Paceliomyces sp., Cladosporium sp. and Sporothrix schenckii were isolated for the first time from Jaipur.Conclusion: Road sides were found most suitable for the occurrence of all most all keratinophilic fungi. Higher incidence of keratinophilic fungi was found in hostel sides followed by road sides, PG study centers and play grounds.